1997
DOI: 10.1046/j.1365-2141.1997.3893203.x
|View full text |Cite
|
Sign up to set email alerts
|

Elevated levels of shed syndecan‐1 correlate with tumour mass and decreased matrix metalloproteinase‐9 activity in the serum of patients with multiple myeloma

Abstract: Summary. Sera from 20 myeloma patients and 12 normal controls were analysed for the presence of syndecan-1 and matrix metalloproteinase-9 (MMP-9). The level of syndecan-1 in the serum was elevated in 7/20 (35%) myeloma patients whilst 6/19 patients (31%) had decreased serum MMP-9 activity. The presence of increased syndecan-1 was associated with decreased serum MMP-9. Both elevated syndecan-1 and decreased MMP-9 were associated with higher marrow plasmacytosis, serum beta-2 microglobulin and paraprotein levels… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
81
0
3

Year Published

2000
2000
2022
2022

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 93 publications
(90 citation statements)
references
References 9 publications
4
81
0
3
Order By: Relevance
“…On MMC, the function of syndecan-1 is not fully elucidated yet. The soluble form of syndecan-1 is detected in the serum of patients with MM (Dhodapkar et al, 1997) and is an indicator of poor prognosis (Klein et al, 1999;Seidel et al, 2000b). Soluble syndecan-1 also accumulates within the tumor BM environment of MM patients (Seidel et al, 2000a;Bayer-Garner et al, 2001).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…On MMC, the function of syndecan-1 is not fully elucidated yet. The soluble form of syndecan-1 is detected in the serum of patients with MM (Dhodapkar et al, 1997) and is an indicator of poor prognosis (Klein et al, 1999;Seidel et al, 2000b). Soluble syndecan-1 also accumulates within the tumor BM environment of MM patients (Seidel et al, 2000a;Bayer-Garner et al, 2001).…”
Section: Discussionmentioning
confidence: 99%
“…Soluble syndecan-1 also accumulates within the tumor BM environment of MM patients (Seidel et al, 2000a;Bayer-Garner et al, 2001). As this soluble form of syndecan-1 is biologically active (Dhodapkar et al, 1997), one can speculate that Gene expression profile of EGF-ligands was determined with Affymetrix U133A+B DNA microarrays in 20 HMCLs. ErbB receptor expression was determined by real-time PCR (Mahtouk et al, 2005).…”
Section: Discussionmentioning
confidence: 99%
“…This unveils an important new mechanism by which heparanase promotes tumor aggressiveness. Studies on samples from myeloma patients reveals that a high level of shed syndecan-1 in the serum is an indicator of high tumor burden and poor prognosis (10,11) and that high heparanase enzyme activity in the bone marrow of myeloma patients correlates with high tumor microvessel density, which is also an indicator of poor prognosis (21). Using in vivo models of myeloma, we have demonstrated that elevation of expression of either soluble syndecan-1 or heparanase promotes tumor growth, angiogenesis, and metastasis (12,13).…”
Section: Discussionmentioning
confidence: 99%
“…Shed syndecan-1 can become lodged and incorporated into the bone marrow extracellular matrix that supports the tumor or remain as a soluble component within the bone marrow plasma. In addition, shed syndecan-1 accumulates in the sera of myeloma patients, where high serum levels of syndecan-1 reflect a high tumor burden and predict poor prognosis (10,11).…”
mentioning
confidence: 99%
“…Transfection or induction of syndecan-1 by PR-39, a proline-rich antimicrobial peptide, suppresses invasive activity of hepatoma cells suggesting that it may serve as a basis for drug designing or gene therapy e ective against metastasis of hepatocellular carcinomas (Fujimoto and Kohgo, 1998). The addition of intact puri®ed syndecan-1 to myeloma and bone marrow cells in culture has been shown to induce apoptosis, dose-dependent growth inhibition and decrease in osteoblastogenesis (Dhodapkar et al, 1998;Dhodapkar and Sanderson, 1999). Decorin, a member of the small leucine-rich dermatan/chondroitin sulfate proteoglycan (SLRP) gene family is maximally expressed in quiescent cells, not detectable in transformed ones and down regulated in many tumors.…”
Section: Chromosomal Assignment Of Gros1mentioning
confidence: 99%